PENINGKATAN PELAYANAN KESEHATAN MASYARAKAT SEBAGAI IMPLIKASI KINERJA PEGAWAI DI PUSKESMAS TAMMERO’DO KECAMATAN TAMMERO’DO KABUPATEN MAJENE - Aco Dahrul Saharuddin (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2017)
This study aims to look at improving employee performance in the form of health services to the community at Tammero’do health center. The research method used is descriptive qualitative, that is to give an accurate description or explanation objectively regarding the actual state of the object under study. Data collection instruments are interviews and observations on location and also based on documents / records / reports and legislation relating to the problem under study. The focus of this research is based on the aspects of puskesmas services. The results of this study indicate how the efforts of employees or health centers in improving services provided to employees in which there is an increase in primary level services and improvement of secondary services and improvement of tertiary services.